2017
DOI: 10.1016/j.rmcr.2017.04.009
|View full text |Cite
|
Sign up to set email alerts
|

A case of intravascular large B-cell lymphoma of lung presenting with progressive multiple nodules on chest computed tomography

Abstract: A 71-year-old man was admitted to our hospital for dyspnea, which had worsened over a period of more than six months. He was previously diagnosed as having cryptogenic organizing pneumonia, and was treated with steroids in another hospital. He had complained of worsening dyspnea, despite the treatment. We performed video-assisted thoracoscopic surgery because of the high level of lactate dehydrogenase and inconsistency of the usual interstitial pneumonia pattern. Pathologic specimens showed atypical lymphocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…It is known to be useful to diagnose lung IVL by transbronchial lung biopsy [ 3 , [8] , [9] , [10] ], but others reported that TBLB could not be performed because of hypoxemia during examination [ 11 ]. Since lung primary or predominant form of IVLBCL has poor prognosis [ 12 , 13 ], early diagnosis is needed.…”
Section: Discussionmentioning
confidence: 99%
“…It is known to be useful to diagnose lung IVL by transbronchial lung biopsy [ 3 , [8] , [9] , [10] ], but others reported that TBLB could not be performed because of hypoxemia during examination [ 11 ]. Since lung primary or predominant form of IVLBCL has poor prognosis [ 12 , 13 ], early diagnosis is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Definitive diagnosis needs to be established by histopathological examination. Radiological presentation of IVBCL on CT scan of the chest can be nonspecific, ranging from normal, ground glass, to solitary or diffuse multiple small nodules [[8], [9], [10],16]. Tissue biopsies such as surgical lung biopsy, random transbronchial lung biopsy, CT guided percutaneous lung biopsy, skin biopsy, percutaneous renal biopsy are among the different modalities documented to have been used to obtain a pathological diagnosis of IVBCL with pulmonary presentation [8].…”
Section: Discussionmentioning
confidence: 99%
“…Radiological imaging plays a little role in diagnosis of IVLBCL with absence of lymphadenopathy as in our cases [ 12 , 13 ]. Imaging of the abdomen frequently showed splenomegaly, which was also found in two of our three patients.…”
Section: Discussionmentioning
confidence: 99%